PENGEMBANGAN PANDUAN TEKNIK MENDONGENG UNTUK MENINGKATKAN DISIPLIN DIRI ANAK RA/PAUD/TK - Nurhayati, Nurhayati; Faijin, Faijin (Educatio, 2019)
The purpose of this study is to produce a storytelling guide to improve the self-discipline of RA / PAUD / TK students who have fulfilled the theoretical and practical aspects of acceptance. The development of storytelling guidelines to improve the self- discipline of RA / PAUD / TK students is an adaptation of the Borg & Gall (1983) research and development model, which was modified into three stages: 1) phase I: assessment and literature study, 2) phase II product development: formulating competency goals and standards, compiling indicators, compiling initial drafts, 3) phase III (testing): product validation (guidance and counseling expert, instructional media development expert, & user), and effectiveness testing in limited fields. Data collection instruments used were: product assessment questionnaire and self-discipline checklist. Quantitative data were analyzed by non-parametric statistics, while input / criticism / suggestions from experts were analyzed by qualitative descriptive analysis. The results of the assessment of theorists and user experts, of the storytelling guide to improve the self-discipline of RA / PAUD / TK students, have fulfilled the theoretical and practical acceptability element. The results of field trials show that this practical and effective storytelling guide is used to improve self-discipline.